Direct Conversion of Human Pluripotent Stem Cells to Osteoblasts With a Small Molecule. (28th February 2018) - Kang, Heemin; Shih, Yu‐Ru V.; Varghese, Shyni
Abstract: Human pluripotent stem cells (hPSCs), which exhibit unlimited self‐renewal ability and can differentiate into all cell types in the human body, are a promising cell source for cell‐based therapies and regenerative medicine. Small molecules hold great potential in the derivation of tissue‐specific cells from hPSCs owing to their cost‐effectiveness and scalability. Here, we describe a protocol for deriving osteoblasts from hPSCs by using a single, natural small molecule: adenosine. This simple and effective experimental protocol allows one to obtain large numbers of osteoblasts or osteoprogenitor cells, with the ability to form functional bone tissues, from hPSCs, including human embryonic stem cells and induced pluripotent stem cells. This protocol could potentially enable studies of tissue regeneration and skeletal diseases. © 2018 by John Wiley & Sons, Inc.